Mulheres na política: estereotipia, sexismo e posicionamento político - Sousa, Amanda Wanderley Leite de (2021)
This dissertation aimed to investigate the influence of the political positioning of female candidates (e.g. conservative/center/progressive) and ambivalent sexism in the attribution of stereotypes to these candidates for elective positions to the national congress. To achieve this goal, two experimental studies were carried out. The results of Study 1 (N = 112) show that, together, the right-wing candidate received a lower score than the center and left-wing candidates in the three stereotypical dimensions (morality, sociability and competence), with no differences between these two latest candidates. In Study 2 (N = 129) it was analyzed whether the attribution of stereotypes is influenced by the degree of adherence to hostile or benevolent sexism. The results showed that, among people with a low degree of adherence to benevolent sexism, the left-wing candidate was seen as having more moral attributes than the center candidate and the right-wing candidate was seen as having fewer moral attributes than the other two. People with low adherence to benevolent sexism also showed significant differences in the attribution of stereotypes of sociability and competence among the candidates in all conditions. In this way, the left-wing candidate was seen as having more attributes of sociability and competence than the center candidate and the rightwing candidate was seen as having less sociability and competence attributes than the other two. Among participants with a low degree of adherence to hostile sexism, the left-wing and center candidates were seen to be equally moral, competent and sociable and the right-wing candidate as being less moral, competent and sociable than the other two. It is noteworthy, however, that there were no significant differences between the candidates in the situation of hostile and benevolent high sexism. Taken together, the results of the two studies carried out show the importance of both social belongings and ideologies (e.g. ambivalent sexism) in the attribution of stereotypes.